Interventional radiology cases - Covey, Anne M.; Pua, Bradley; Aguado, Allison; Madoff, David C. ([New York] : Oxford University Press, 2015)
In 104 cases featuring over 500, high-quality images, this book is a thorough and accessible review of the interventional procedures that radiology residents are expected to be familiar with upon completion of residency and general radiologists need to know for recertification examinations.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Interventional radiology -- Case studies